Antitumor Effect of Supercritical CO Extract of Mango Ginger ( Roxb) in U-87MG Human Glioblastoma Nude Mice Xenografts - Cheppail Ramachandran PhD, MBA; Gilda M. Portalatin BS; Adriana M. Prado BS; Karl-Werner Quirin PhD; Enrique Escalon MD; Steven J. Melnick PhD, MD (SAGE Publishing, 2017)
Glioblastoma multiforme (GBM) is one the most aggressive and lethal human neoplasms with poor prognosis and very limited positive treatment options. The antitumor effect of supercritical CO 2 extract of mango ginger ( Curcuma amada Roxb) (CA) with and without irinotecan (IR) was analyzed in U-87MG human glioblastoma multiforme (GBM) cells in vitro and in nude mice xenografts. CA is highly cytotoxic to GBM cells and is synergistic with IR as indicated by the combination index values of <1 in the CompuSyn analysis. CA inhibits tumor growth rate in GBM xenografts, the inhibition rate being higher than in IR treated group. GBM xenograft mice treated with IR + CA combination showed almost complete inhibition of tumor growth rate. Gene expression analysis of xenograft tumors indicated that IR + CA treatment significantly downregulated anti-apoptotic (Bcl-2 and mutant p53), inflammation-associated (COX-2) and cell division-associated (CCNB2) genes and upregulated pro-apoptotic genes (p21 and caspase-3). These results confirmed the therapeutic efficiency of IR + CA combination against GBM and the need for further clinical investigations.